Coplanar Electrode Polymer Modulators Incorporating Fluorinated Polyimide Backbone Electro-Optic Polymer - Eun-Su Lee; Sung-Moon Kim; Mi-Hye Yi; Jae-Won Ka; Min-Cheol Oh (Photonics, 2020)
High-speed coherent optical communication has been expanding to handle the ever-increasing data traffic, and the large modulation bandwidth of electro-optic (EO) polymer modulators has been especially appreciated. However, to be useful in optical communication, the EO polymer device should address several issues, such as thermal stability, photo-oxidation, and bias drift. In this work, as a part of the experiments to address these challenges, an EO polymer with a fluorinated polyimide backbone is utilized to create EO polymer modulators with improved thermal stability. A coplanar electrode structure is introduced to enhance the poling efficiency and reduce the bias drift.